1978
DOI: 10.1111/j.1600-0447.1978.tb06890.x
|View full text |Cite
|
Sign up to set email alerts
|

L‐Tryptophan and 5‐hydroxytryptophan in the treatment of depression

Abstract: Trials performed do not provide evidence for an antidepressant effect of 5-HTP. L-TP, without interacting pharmaca, does not appear to be a well-documented antidepressant. The only convincing evidence for L-TP as an antidepressant is that L-TP enhances the effect of MAOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In patients, tryptophan augmentation of 5-HT reuptake therapy is supported by a limited number of clinical trials [47], [48]. These data are, however, not definitive [46], [50] and large follow-up clinical trials have not been reported. In an animal model, behavioral and physiological relevance of the suppression of 5-HT synthesis by SSRIs could be assessed by augmenting 5-HT synthesis in SSRI-treated animals using tryptophan loading [92].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients, tryptophan augmentation of 5-HT reuptake therapy is supported by a limited number of clinical trials [47], [48]. These data are, however, not definitive [46], [50] and large follow-up clinical trials have not been reported. In an animal model, behavioral and physiological relevance of the suppression of 5-HT synthesis by SSRIs could be assessed by augmenting 5-HT synthesis in SSRI-treated animals using tryptophan loading [92].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of 5-HT synthesis can induce a rapid relapse of depression symptoms in SSRI-treated patients with remitted depression, an effect which is not readily observed in subjects with no history of SSRI administration [27], [37][44] (also see [45]). Tryptophan itself is considered to be ineffective as an antidepressant [46]; however, tryptophan co-administered with a 5-HT reuptake inhibitor may be more effective as an antidepressant than the reuptake inhibitor administered alone [47][50].…”
Section: Introductionmentioning
confidence: 99%
“…the amino acid precursor of serotonin, with good results. Tryptophan has also been shown by some inves tigators to have antidepressant efficacy [D'Elia et al, 1978]. Additionally, Asberg et al [1976] have posited a biochemical subtype of depression marked by a serotonin deficiency.…”
Section: Pharmacologic Evidencementioning
confidence: 99%
“…However, clinical trials in which patients have been administered tryptophan or 5-HT have given conflicting results and reached differing conclusions [10,12,[15][16][17]. They also have side-effects (commonly nausea and gastrointestinal distress) [14].…”
mentioning
confidence: 99%